A Successful Nodular Basal Cell Carcinoma Defect Closure On The Mid-Cheek Using Modified Mini Cheek Advancement Flap - Widjaya MRH; Koswara T (Cancer Management and Research, 2025)
Muhamad Radyn Haryadi Widjaya,1 Teja Koswara2 1Department of Dermatology and Venereology, Hamori Hospital, Subang, West Java, Indonesia; 2Department of Anatomical Pathology, Faculty of Medicine, Universitas Jenderal Achmad Yani, Cimahi, West Java, IndonesiaCorrespondence: Muhamad Radyn Haryadi Widjaya, Department of Dermatology and Venereology, Hamori Hospital, Jl. Raya Sembung Pagaden, Subang, West Java, 41251, Indonesia, Tel +6282129347686, Email radynmuhamad@gmail.comAbstract: Basal cell carcinoma (BCC) is the most common type of malignant skin tumour. This skin cancer is further divided into pigmented, morpheaform, superficial, and nodular BCC (nBCC), as well as fibroepithelioma of Pinkus. Despite its slow growth and very rare metastases, BCC might cause morbidity due to its tendency to relapse as well as its locally invasive nature, especially when located on the face. Wide local excision might be an effective treatment option for BCC and is usually followed by a surgical defect reconstruction procedure. We report a case of 61-year-old woman who presented with a superficially ulcerated, well-defined, hyperpigmented nodule with a rolled edge and frequent episodes of bleeding, as well as suppuration on the right mid-cheek in the past year before the consultation. The lesion was excised and the sample was sent for histopathological examination, revealing tumour mass in a palisading arrangement at the edges, forming solid islands, which is consistent with the diagnosis of nBCC with tumour-free edges. Defect closure with the mini cheek advancement flap (mini-CAF) technique yielded good results after eight months without any recurrence in one year. Skin flap techniques vary widely, among them is the cheek advancement flap technique which might be used for reconstructing defects on the mid-cheek. This flap technique can be modified as mini-CAF by placing a flap incision on the natural creases of the mid-cheek, namely the palpebromalar and nasojugal creases. Mini-CAF offer the advantage as its ability to camouflage the excision line by utilising the natural creases of the face, thus resulting in an aesthetically and functionally favourable result.Keywords: basal cell carcinoma, defect closure, mini cheek advancement flap, nasojugal crease, palpebromalar crease